Xây dựng bài toán loại trừ dịch chuyển không - điều khiển trong vùng đặc biệt của tay máy song song - Nguyen, Minh Thạnh; Nguyen, Ngọc Lâm; Tran , Công Tuấn; Nguyen, Công Mậu (Journal of Technical Education Science, 2007)
The approach to singularity configurations of the parallel manipulator is represented which supposes to consider the degree of freedom of the final output link and the quan- tity of the kinematic subchains connecting the base and the output link. The theorem of A.P. Kotelnikov is used in order to exclude non-controlled mobility of the output link. How to avoid infinitesimal non-controlled mobility in singularity configurations is considered